2017
DOI: 10.1016/j.taap.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of TCDD-induced AhR-mediated gene expression in human, mouse and rat primary B cells

Abstract: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a persistent environmental pollutant that activates the aryl hydrocarbon receptor (AhR) resulting in altered gene expression. In vivo, in vitro, and ex vivo studies have demonstrated that B cells are directly impaired by TCDD, and are a sensitive target as evidenced by suppression of antibody responses. The window of sensitivity to TCDD-induced suppression of IgM secretion among mouse, rat and human B cells is similar. Specifically, TCDD must be present within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Before inferring if TCDD and presence/absence of SFB would have a similar influence on humans compared to the murine model, both the host and microbial phenotype must be considered. Differences in host phenotype have been described previously ( Kreisman and Cobb, 2011 ), with varied gene expression in response to TCDD depending on the measured tissue and host species ( Kovalova et al, 2017 ). In regards to microbiota, recent meta-analysis has shown that 90 and 89% of bacterial phyla and genera, respectively, are shared between mice and the human gut microbiota ( Krych et al, 2013 ), with the most abundant bacterial species being common in both.…”
Section: Discussionmentioning
confidence: 62%
“…Before inferring if TCDD and presence/absence of SFB would have a similar influence on humans compared to the murine model, both the host and microbial phenotype must be considered. Differences in host phenotype have been described previously ( Kreisman and Cobb, 2011 ), with varied gene expression in response to TCDD depending on the measured tissue and host species ( Kovalova et al, 2017 ). In regards to microbiota, recent meta-analysis has shown that 90 and 89% of bacterial phyla and genera, respectively, are shared between mice and the human gut microbiota ( Krych et al, 2013 ), with the most abundant bacterial species being common in both.…”
Section: Discussionmentioning
confidence: 62%
“…Analysis of TCGA/SKCM data was performed using OncoLnc portal [ http://www.oncolnc.org ] 62 . The raw data count matrix composed of 479 samples; from SKCM melanoma cohort was downloaded from the OncoLnc for the pigmentation genes ( n = 14) 12 , the AhR target genes ( n = 19) 63 , or the BRAFi resistant genes ( n = 19) 17 . Expression heatmap of differentially expressed genes between samples was obtained on log2 fold change using heatmap3 package in R/Bioconductor.…”
Section: Methodsmentioning
confidence: 99%
“…The cytochrome P450 isoenzyme CYP1A1 had concordant increased expression regardless of the species and tissue. 86 …”
Section: Current Systems Biology Methods Used In Toxicogenomicsmentioning
confidence: 99%